Projeto de um equipamento de elevação, transporte e manutenção para mini baja - Góis, Pedro Luis Rocha de (Universidade Federal Rural do Semi-Árido, 2020)
In the present project to conclude the course, several aspects of the project were addressed for the development of equipment for lifting, transporting and maintaining offroad vehicles. For that, an acquisition of information about load was carried out, as well as the time of use of the equipment. In addition, calculations were made for sizing, use of software for dynamic and static alteration of the project, linking to post-analysis improvements. First, the conceptual design was carried out, in parallel with a bibliographic review, the application of the mechanical design, for later calculation memorial, with all the measures, materials and cost estimate for using the equipment. The work was based on three methods, by different authors, seeking to link to the points considered positive in each of them, in addition to consulting technical catalogs of manufacturers and authors in the field of machine design.
Keywords: Projeto; Pórtico rolante; Projeto de máquinas; Project; Moving gantry; Machine design; ENGENHARIAS::ENGENHARIA MECANICA